1995
DOI: 10.1007/bf02214873
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acid suppression on microbial flora of upper gut

Abstract: Decreased acid secretion, due to therapy or disease, predisposes to increased bacterial counts in gastric juice. As bacterial numbers increase, the number of nitrate-reducing strains and the concentration of luminal nitrite usually also increase. However, there is controversy (mainly because of assay problems) about whether decreased acid increases generation of N-nitroso compounds: these may be produced by acid or by bacterial catalysis, and the relative contributions of each are still uncertain. Other potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 110 publications
1
30
0
Order By: Relevance
“…54 Studies found a logarithmic relationship between intragastric pH and median bacterial counts in the gastric juice and mucosa and increased risks for enteric infections and bacterial diarrhea. 55,56 A review of the literature notes that multiple non-H. pylori organisms have been isolated from the stomach in hypochlorhydric patients, including Lactobacillus spp, Streptococcus spp, Pseudomonas spp, Xanthomonas spp, Proteus spp, Klebsiella spp, Neisseria spp, Escherichia coli, and Campylobacter jejuni. 54 Acid suppressive drugs also affect the progression of H. pylori pathogenesis.…”
Section: Gastric Perturbations By Helicobacter Pylorimentioning
confidence: 99%
“…54 Studies found a logarithmic relationship between intragastric pH and median bacterial counts in the gastric juice and mucosa and increased risks for enteric infections and bacterial diarrhea. 55,56 A review of the literature notes that multiple non-H. pylori organisms have been isolated from the stomach in hypochlorhydric patients, including Lactobacillus spp, Streptococcus spp, Pseudomonas spp, Xanthomonas spp, Proteus spp, Klebsiella spp, Neisseria spp, Escherichia coli, and Campylobacter jejuni. 54 Acid suppressive drugs also affect the progression of H. pylori pathogenesis.…”
Section: Gastric Perturbations By Helicobacter Pylorimentioning
confidence: 99%
“…Furthermore, given a pH v4, ascorbic acid in the gastric juice competes for the nitrosation species instead of converting them to nitric oxide (NO). Formation of N-nitrosamines does not increase during long-term PPI treatment (for instance 20-40 mg omeprazole daily) [86]; long-term treatment is generally considered safe in man [109]. However, extended follow-up periods are still desirable [110], especially since today's regimes are much more aggressive.…”
Section: Nitrosaminesmentioning
confidence: 98%
“…The molecular events underlying gastric carcinogenesis are still poorly understood, but seem to be a multistep process, as suggested by Correa [84]. Complete blockade of acid secretion may thus be undesirable, as this favours bacterial overgrowth [85,86] and subsequent generation of carcinogenic substances [87,88]. Among these are the N-nitrosamines, which can be found in increased amounts in achlorhydric patients [89,90].…”
Section: Gastric Infectionsmentioning
confidence: 99%
“…This is also known to occur within the oral and gut flora. Nitrite is formed from nitrate by the reductive activity of commensal bacteria in the oral cavity to end up via swallowed saliva as acidified nitrite in the stomach (Correa et al, 1975;Duncan et al, 1995;McKnight et al, 1997;Yeomans et al, 1995). It has been proposed that this nitrite has antimicrobial properties (McKnight et al, 1999).…”
Section: Nitrite and Nitrate Formationmentioning
confidence: 99%